Fragile by design : the political origins of banking crises and scarce credit - Calomiris, Charles W. (Princeton economic history of the Western world., 2014)
Why are banking systems unstable in so many countries--but not in others? The United States has had twelve systemic banking crises since 1840, while Canada has had none. The banking systems of Mexico and Brazil have not only been crisis prone but have provided miniscule amounts of credit to business enterprises and households. Analyzing the political and banking history of the United Kingdom, the United States, Canada, Mexico, and Brazil through several centuries, Fragile by Design demonstrates that chronic banking crises and scarce credit are not accidents due to unforeseen circumstances. Ra.